Spatial and Temporal Dynamics in the Ionic Driving Force for GABAA Receptors - R. Wright; J. V. Raimondo; C. J. Akerman (Neural Plasticity, 2011)
It is becoming increasingly apparent that the strength of GABAergic synaptic transmission is dynamic. One parameter that can establish differences in the actions of GABAergic synapses is the ionic driving force for the chloride-permeable GABAA receptor (GABAAR). Here we review some of the sophisticated ways in which this ionic driving force can vary within neuronal circuits. This driving force for GABAARs is subject to tight spatial control, with the distribution of Cl− transporter proteins and channels generating regional variation in the strength of GABAAR signalling across a single neuron. GABAAR dynamics can result from short-term changes in their driving force, which involve the temporary accumulation or depletion of intracellular Cl−. In addition, activity-dependent changes in the expression and function of Cl− regulating proteins can result in long-term shifts in the driving force for GABAARs. The multifaceted regulation of the ionic driving force for GABAARs has wide ranging implications for mature brain function, neural circuit development, and disease.